Effect of Toll Road Construction Cikampek-Palimanan on Socio-Economic in Kalijati District of Subang Regency - Suci Puji Astuti; Epon Ningrum; Jupri Jupri (USN Kolaka, 2020)
Kalijati sub district is a district with the largest land area is 1002.96 m2 and the number of people at most that 536 people affected by the construction of toll roads Cikampek-Palimanan. In general, the condition of the land affected by the construction of the toll road is a residential area and garden. Based on the authors wanted to examine the effect of highway construction Cikampek-Palimanan on the socioeconomic conditions that include livelihood, income, and ownership of community residences district of Kalijati after land acquisition. The method used in this research is descriptive method. The population is all the people affected by the district Kalijati toll road construction. The sample area is bypassed villages Cikampek toll road development in Cikampek-Palimanan Caracas Village, Village Ciruluk, Kaliangsana Village, and the Village Marengmang. Population sample as many as 85 landowner. The sampling technique used in this study is proportional random sampling. Variables consisted of independent variables which include land, land prices, land types and the dependent variable consisted of socio-economic conditions. Instruments in the study comprised interviews and questionnaires. Data analysis using Chi-square and contingency. The results showed no effect of highway construction Cikampek-palimanan the principal livelihood and sideline, this is due to land in the District Kalijati land use average form settlements and gardens, in addition to the District of Kalijati few people who use the proceeds from the sale of land for opening a new business, for example opening a store or make a contract, There are significant road construction Cikampek-palimanan to influence people's income shows the value by 21% because the affected area is the construction of toll roads productive land and and there are significant road construction Cikampek-dwelling palimanan to show the influence of ownership by 32% because of the sale of public land use average to build and repair houses. Thus the construction of toll roads Cikampek-palimanan the socioeconomic conditions of the people in District Kalijati not have influence on the principal livelihood and livelihood while the side shows the influence of the income and ownership of residence in District Kalijati.